Zapisz wyrażenia bez nawiasó wi wykonaj ich redukcje wyrazow podobnych
a) (2x - 3) - (x² - 3x + 1) + (3x ² - 6x - 5)=
b) (0,5 a² +a ) + (0,7 a² - 3a + 1 +
- (-0,2 a ² + 1,2 a - 1,5) =
c) -( 2a + 3b) - (2b-ab) + (5a- 2ab) +
- (-5b + 4ab) =

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T23:22:40+01:00
A) (2x - 3) - (x² - 3x + 1) + (3x ² - 6x - 5)=2x-3-x²+3x-1+3x²-6x-5=-2x²-x-9
b) (0,5 a² +a ) + (0,7 a² - 3a + 1 - (-0,2 a ² + 1,2 a - 1,5) =0,5a²+a+0,7a²-3a+1+0,2a²-1,2a+1,5=1,4a²-3,2a+2,5
c) -( 2a + 3b) - (2b-ab) + (5a- 2ab) - (-5b + 4ab) =-2a-3b-2b+ab+5a-2ab+5b-4ab=3a-5ab
2010-03-25T23:25:46+01:00
A]
(2x-3)-(x²-3x+1)+(3x²-6x-5)=
2x-3-x²+3x-1+3x²-6x-5=
2x²-x-9

b]
(0,5a²+a)+(0,7a²-3a+1)+-(-0,2a²+1,2a-1,5)=
0,5a²+a+0,7a²-3a+1+0,2a²-1,2a+1,5=
1,4a²-3,2a+2,5

c]
-(2a+3b)-(2b-ab)+(5a-2ab)+-(-5b+4ab)=
-2a-3b-2b+ab+5a-2ab+5b-4ab=
3a-5ab